An electronic, smart lighter to measure cigarette smoking: A pilot study to assess feasibility and initial validity. (November 2019) - Tomko, Rachel L.; McClure, Erin A.; Cato, Patrick A.; Wang, Julie B.; Carpenter, Matthew J.; Karelitz, Joshua L.; Froeliger, Brett; Saladin, Michael E.; Gray, Kevin M.
Abstract: Understanding variability in smoking patterns may inform smoking cessation interventions. Retrospective reports of cigarettes smoked per day may be biased and typically do not provide temporal precision regarding when cigarettes are smoked. However, real-time, user-initiated tracking, such as logging each time a cigarette is smoked, can be burdensome over long time frames. In this study, adult, non-treatment seeking daily smokers ( N = 22) used an electronic, smart lighter to light and timestamp cigarettes for 14 days. Participants reported number of cigarettes smoked per day (CPD) via a mobile device (daily diary) and retrospectively reported CPD at the end of the study using the Timeline Followback (TLFB). Self-reported lighter satisfaction and adherence varied with 68% of participants reporting that they liked using the lighter and participants reporting using the lighter for 92% of cigarettes smoked, on average. Lighter-estimated CPD did not differ from daily diary-estimated CPD, but was significantly lower than TLFB estimates. The lighter resulted in greater day-to-day variability relative to other methods and fewer rounded cigarette counts (digit bias) relative to the TLFB. The lighter appears to be feasible for capturing data on smoking patterns in daily smokers. Though false positive cigarettes are likely low, additional technologies that augment data captured from the lighter may be necessary to reduce false negatives (missed cigarettes) and alternative lighter designs may appeal more to certain smokers. Highlights: An electronic, smart lighter can be feasibly used to track smoking for 14 days. Smokers reported moderate to high satisfaction with the electronic lighter. Smokers reported using the lighter for 92% of cigarettes smoked. Lighter-assessed cigarettes per day were similar to daily diary reported estimates. The lighter estimated greater variability in cigarettes per day and less digit bias.